2016
DOI: 10.5539/jsd.v9n2p78
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Generation Y Employees’ Intention to Quit in Malaysian’s Business Process Outsourcing Sector

Abstract: This paper investigates the factors contributing to Generation Y employees' intention to quit in the business process outsourcing sector (BPO) in Malaysia from four different perspectives: personnel dimensions (work overload, role ambiguity and job stress), job attitudes (satisfaction with pay and organizational commitment), work-life conflict and organizational strategies (training, career planning and empowerment). A structural equation modelling approach was employed to identify the variables that significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
1
17
0
2
Order By: Relevance
“…However, several studies conducted in the West show contradictory evidence reporting that compensation has no significant impact on OC (Bhagat & Chassie, 1981;Malhorta, Budhwar, & Prowse, 2007;Shore & Barksdale, 1998). In Malaysian settings, some studies found that financial compensation and OC were positively correlated (Ibrahim & Boerhaneoddin, 2010;Kee, Ahmad, & Abdullah, 2016;Normala, 2010;Queiri & Dwaikat, 2016). This leads us to the following hypothesis:…”
Section: Satisfaction With Personnel Evaluationmentioning
confidence: 97%
See 2 more Smart Citations
“…However, several studies conducted in the West show contradictory evidence reporting that compensation has no significant impact on OC (Bhagat & Chassie, 1981;Malhorta, Budhwar, & Prowse, 2007;Shore & Barksdale, 1998). In Malaysian settings, some studies found that financial compensation and OC were positively correlated (Ibrahim & Boerhaneoddin, 2010;Kee, Ahmad, & Abdullah, 2016;Normala, 2010;Queiri & Dwaikat, 2016). This leads us to the following hypothesis:…”
Section: Satisfaction With Personnel Evaluationmentioning
confidence: 97%
“…Empirical work typically finds a strong relationship between role clarity and OC in the West (Mathieu & Zajac, 1990), in China (Miao, Newman, Sun, & Xu, 2013;Newman & Sheikh, 2012), in Japanese expatriates (Gregersen & Black, 1996), in foreign employees of an American multinational company (Palich, Hom, & Griffeth, 1995), etc. Several research conducted in Malaysia is also supportive (Karim, 2010;Queiri & Dwaikat, 2016).…”
Section: Role Claritymentioning
confidence: 99%
See 1 more Smart Citation
“…Psikohumaniora: Jurnal Penelitian Psikologi -Vol 3, No 2 (2018) │ 155 bisnis dan kesehatan (Filiana, 2016;Lub, Bijvank, Bal, Blomme, & Schalk, 2012;Nusair, Parsa, & Cobanoglu, 2011;Queiri & Dwaikat, 2016), sementara pada organisasi pendidikan masih jarang dilakukan. Akan tetapi, pada kenyataannya komitmen organisasi di institusi pendidikan juga tak kalah pentingnya.…”
Section: Komitmen Organisasi Pada Dosen Generasi Milenialunclassified
“…Based on past research, the intention to stay is related to various constructs. Queiri and Dwaikat (2016) identified constructs such as training, empowerment, organizational commitment, and lack of career planning. Choi et al (2012) identified that emotional exhaustion, depersonalization, and reduced personal accomplishment increased turnover intentions.…”
mentioning
confidence: 99%